Flame-retardant gel polymer electrolyte as well as preparation method and application thereof
By forming a cross-linked flame-retardant gel polymer electrolyte in situ on the electrode surface of a supercapacitor, the problem of poor contact between the solid electrolyte and the electrode is solved, achieving high efficiency in flame retardancy and low interfacial impedance, ensuring the safe and stable operation of the supercapacitor in extreme environments.
Patent Information
- Application Number
- CN202511582811.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-31
- Publication Date
- 2026-01-27
AI Technical Summary
When existing solid electrolytes come into contact with the electrodes of supercapacitors, they are prone to forming interfacial voids, resulting in high interfacial impedance, low ionic conductivity, and a risk of combustion, which limits their application in high energy density and extreme environments.
A flame-retardant gel polymer electrolyte is used. By forming a cross-linked structure in situ on the electrode surface, and using diethyl iodomethyl phosphate and 1,3-propanesulfonate lactone as additives, a synergistic flame-retardant mechanism of iodine and phosphorus is formed. Combined with a low-viscosity liquid precursor to wet the electrode pores and heat to form a gel network, a tight bond with the electrode is achieved.
It significantly reduces interfacial impedance, improves flame retardant performance, ensures good interfacial compatibility between electrolyte and electrode, guarantees efficient lithium-ion migration, eliminates combustion risks, and achieves safe, stable, and high-energy-density operation.
Smart Images

Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of supercapacitor technology, specifically relating to flame-retardant gel polymer electrolytes, their preparation methods, and applications. Background Technology
[0002] Currently, supercapacitors are making breakthroughs towards higher energy densities, and their applications have gradually expanded from traditional consumer electronics to key areas such as new energy vehicles (e.g., start-stop systems, regenerative braking modules) and large-scale energy storage (e.g., grid peak shaving, renewable energy consumption). These applications place stringent demands on the reliability of supercapacitors: new energy vehicles may encounter extreme environments such as high temperatures and direct sunlight during operation, while large-scale energy storage systems need to withstand high loads for extended periods. This makes the safety of supercapacitors increasingly prominent, becoming a key bottleneck restricting their large-scale application in core areas.
[0003] Traditional supercapacitors generally use liquid electrolytes, which are mainly composed of organic solvents such as carbonates. These electrolytes have inherent drawbacks such as low flash point and high volatility. When a supercapacitor experiences abnormal conditions such as thermal abuse (e.g., internal Joule heat accumulation), overcharging (electrode side reactions causing heat generation), or internal short circuits (diaphragm damage leading to direct contact between positive and negative electrodes), the organic solvents can easily vaporize rapidly, causing the device casing to rupture, electrolyte leakage, and potentially leading to combustion or even explosion. This not only causes irreversible damage to the equipment but also significantly shortens its lifespan, severely hindering the widespread application of supercapacitors in demanding applications.
[0004] To overcome these challenges, solid-state electrolytes, with their core advantages of being leak-free and flame-retardant, have become an ideal alternative to traditional liquid electrolytes. However, most existing solid-state electrolytes are rigid systems, while supercapacitor electrodes (such as activated carbon electrodes) typically have high porosity (over 70%) and high surface roughness, leading to interfacial voids and poor contact when the rigid solid-state electrolyte comes into contact with the electrode. This interfacial defect directly causes key technical challenges such as significantly increased interfacial impedance and low ionic conductivity, limiting the practical application of solid-state electrolytes. Therefore, it is urgent to further improve the safety performance of electrolytes through flame-retardant modification technology, while optimizing the interfacial compatibility between the electrolyte and the electrode, to ensure that supercapacitors can achieve safe, stable, and long-cycle operation under extreme conditions, providing core support for their development towards higher energy densities. Summary of the Invention
[0005] In order to overcome the shortcomings of the prior art, the present invention aims to provide flame-retardant gel polymer electrolytes, their preparation methods and applications, so as to solve the technical problem that the flame-retardant ability of solid electrolytes needs to be improved.
[0006] To achieve the above objectives, the present invention employs the following technical solution: The first aspect of this invention discloses a method for preparing a flame-retardant gel polymer electrolyte, comprising the following steps: 1) Add diethyl iodomethyl phosphate and 1,3-propanesulfonate lactone to an organic solvent containing 1,3-dioxolane and mix well to obtain a mixed solution; 2) Add lithium salt to the mixed solution obtained in step 1) to obtain the precursor solution; 3) The precursor solution obtained in step 2) is dropped onto the electrode surface and assembled into a supercapacitor. Heating is then performed to form a flame-retardant gel polymer electrolyte in situ on the electrode surface.
[0007] Preferably, in step 1), the organic solvent containing 1,3-dioxolane is a mixed solution of 1,3-dioxolane and carbonate solvent.
[0008] More preferably, the carbonate solvent includes chain carbonates and cyclic carbonates; based on the total volume of the organic solvent (100%), the organic solvent containing 1,3-dioxolane includes 50% to 60% 1,3-dioxolane, 20% to 30% chain carbonates, and 20% to 25% cyclic carbonates.
[0009] More preferably, the chain carbonate includes at least one of diethyl carbonate and dimethyl carbonate, and the cyclic carbonate includes fluoroethylene carbonate and ethylene carbonate.
[0010] Preferably, in step 2), the lithium salt is lithium hexafluorophosphate.
[0011] Preferably, in step 3), the heating temperature is 60~90℃.
[0012] Preferably, in the precursor solution, the amount of diethyl iodomethyl phosphate added is 3%~7% by mass percentage, the amount of 1,3-propanesulfonate lactone added is 0.3%~1%, the amount of lithium salt added is 12%~15%, and the balance is an organic solvent containing 1,3-dioxolane.
[0013] In a second aspect, the present invention discloses a flame-retardant gel polymer electrolyte obtained by the above preparation method.
[0014] A third aspect of the present invention discloses the application of the above-mentioned flame-retardant gel polymer electrolyte in the preparation of supercapacitors.
[0015] A fourth aspect of the present invention discloses a supercapacitor containing a flame-retardant gel polymer electrolyte obtained by the above preparation method.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The flame-retardant gel polymer electrolyte provided by this invention: 1) Uses diethyl iodomethyl phosphate as a super flame-retardant additive. After adding the super flame-retardant additive, iodine free radicals (I·) capture H· and HO· free radicals in the combustion chain reaction, interrupting the chain reaction of the flame. The hydrogen iodide (HI) released by the thermal decomposition of iodine compounds can also dilute oxygen and combustible gases; the phosphorus component decomposes by heat to generate polymetaphosphoric acid and other coverings, forming a heat-insulating and oxygen-barrier carbon layer on the material surface. Iodine and phosphorus elements work synergistically: iodine "extinguishes fire" in the gas phase, and phosphorus "builds walls" in the condensed phase, jointly improving the flame-retardant efficiency; 2) The in-situ polymerization strategy first injects a low-viscosity liquid precursor into the supercapacitor, allowing it to fully wet every pore of the electrode and the separator like a liquid electrolyte; then, by heating, a polymerization reaction is initiated inside the device to form a gel polymer network, achieving a molecular-level tight adhesion with the electrode surface, effectively achieving "seamless interface bonding", thereby significantly reducing interface impedance and ensuring efficient migration of lithium ions. Therefore, the flame-retardant gel polymer electrolyte prepared by this method can not only significantly improve the flame-retardant properties of the electrolyte and fundamentally eliminate the risk of combustion, but also form a good solid-liquid mixing interface with the electrode, ensuring high ionic conductivity and low interfacial impedance. Detailed Implementation
[0017] To enable those skilled in the art to understand the features and effects of the present invention, the following descriptions and definitions are only general descriptions of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in the event of any conflict, the definitions in this specification shall prevail.
[0018] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.
[0019] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values (including integers and fractions) within those ranges.
[0020] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”
[0021] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.
[0022] This invention provides a method for preparing a flame-retardant gel polymer electrolyte, the specific preparation method of which is as follows: S1: Based on the total volume of organic solvent as 100%, in an argon atmosphere glove box, take 50%~60% of 1,3-dioxolane (DOL), 20%~30% of chain carbonate and 20%~25% of cyclic carbonate and mix them to form a homogeneous organic solvent containing 1,3-dioxolane. The chain carbonate includes at least one of diethyl carbonate (DEC) and dimethyl carbonate (DMC), and the cyclic carbonate includes fluoroethylene carbonate (FEC) and ethylene carbonate (EC).
[0023] S2: Add 3%~7% of diethyl iodomethyl phosphate and 0.3%~1% of 1,3-propanesulfonate lactone (PS) to the organic solvent containing 1,3-dioxolane prepared in S1 to obtain a mixed solution. The structural formula of the iodomethyl phosphate diethyl ester is as follows: The structural formula of 1,3-propanesulfonate lactone is: ; S3: Add 12%~15% lithium salt by mass to the mixed solution obtained in S2 to obtain the precursor solution; The lithium salt includes, but is not limited to, lithium hexafluorophosphate; S4: The precursor solution obtained in S3 is dropped onto the electrode surface and assembled into a supercapacitor. The ring-opening polymerization of 1,3-dioxolane (DOL) is initiated by heating to form a high-voltage resistant gel polymer electrolyte with a cross-linked structure in situ on the electrode surface. The heating temperature is 60~90℃, preferably 60~70℃; the preferred supercapacitor model is CR2032.
[0024] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading this description, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0025] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under standard conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications in the art, unless otherwise stated.
[0026] Example 1 The preparation method of flame-retardant gel polymer electrolyte is as follows: Step 1: Preparation of organic solvent mixture solution In an argon-filled glove box (with water and oxygen content below 0.1 ppm), based on a total organic solvent volume of 10 mL, accurately measure 5.5 mL of 1,3-dioxolane (DOL; 55% of the total organic solvent volume), 1.5 mL of diethyl carbonate (DEC; 15% of the total organic solvent volume), 1.0 mL of dimethyl carbonate (DMC; 10% of the total organic solvent volume), 0.5 mL of fluoroethylene carbonate (FEC; 5% of the total organic solvent volume), and 1.5 mL of ethylene carbonate (EC; 15% of the total organic solvent volume). Then, add the above solutions to a clean glass bottle and stir with a magnetic stirrer at 300 rpm for 15 minutes until a clear, homogeneous organic solvent mixture is formed.
[0027] Step 2: Add flame retardant additives and auxiliary additives Add 0.30 g of diethyl iodomethyl phosphate (3% of the total mass of the precursor solution) and 0.03 g of 1,3-propanesulfonate lactone (0.3% of the total mass of the precursor solution) to the organic solvent mixture prepared in step one, and continue stirring at 300 rpm for 20 minutes to ensure that diethyl iodomethyl phosphate and 1,3-propanesulfonate lactone are completely dissolved to obtain a mixed solution.
[0028] Step 3: Preparation of precursor solution Add 1.30 g of lithium hexafluorophosphate (LiPF6; accounting for 13% of the total mass of the precursor solution) to the mixed solution obtained in step 2, and then place the mixed solution on a stirring table and stir at 300 rpm for 30 minutes until the LiPF6 is completely dissolved to obtain a clear, transparent and homogeneous precursor solution.
[0029] Step 4: Assembly and in-situ polymerization of supercapacitors In an argon-filled glove box, the following components were stacked and assembled into a CR2032 coin cell: positive electrode: NCM811 positive electrode sheet (12 mm × 12 mm); negative electrode: natural graphite sheet (12 mm × 12 mm); separator: glass fiber separator (Whatman GF / D, 16 mm × 16 mm); stainless steel sheet; positive electrode shell; negative electrode shell; and spring sheet, in the order of "positive electrode shell → positive electrode sheet → separator → graphite sheet → stainless steel sheet → spring sheet → negative electrode shell". Then, 0.15 mL of the precursor solution prepared in step three was slowly added dropwise to the separator, ensuring the electrolyte fully wetted the separator and electrodes. The coin cell was then press-sealed using a coin cell sealing machine. Finally, the sealed supercapacitor was transferred to a constant-temperature drying oven and left to stand at 60°C for 3 hours. In this process, 1,3-dioxolane (DOL) undergoes ring-opening polymerization under the catalysis of lithium salt (LiPF6), forming a gel with a cross-linked network structure in situ in the precursor solution, thereby obtaining a flame-retardant gel polymer electrolyte.
[0030] Example 2 The only difference between this embodiment and Embodiment 1 is that in step two, the amount of diethyl iodomethyl phosphate added is 4%, while the other steps are the same as in Embodiment 1.
[0031] Example 3 The only difference between this embodiment and Example 1 is that in step two, the amount of diethyl iodomethyl phosphate added is 5%, while the other steps are the same as in Example 1.
[0032] Example 4 The only difference between this embodiment and Example 1 is that in step two, the amount of diethyl iodomethyl phosphate added is 7%, while the other steps are the same as in Example 1.
[0033] Example 5 The only difference between this embodiment and Example 1 is that in step two, the amount of 1,3-propanesulfonate lactone added is 1%, while the rest is the same as in Example 1.
[0034] Comparative Example 1 The only difference between this comparative example and Example 1 is that the precursor solution does not contain diethyl iodomethyl phosphate; otherwise, they are the same as in Example 1.
[0035] Flame-retardant gel polymer electrolytes prepared in Examples 1-5 and Comparative Example 1 were cut into samples with dimensions of 10 mm × 50 mm × 2 mm, with three samples prepared in parallel for each group. The experiment was conducted in a fume hood using an alcohol lamp with an inner diameter of 2 mm, a wick protruding 5 mm, and a flame height adjusted to 20 mm. One end of the sample was held with tweezers, and the other end was vertically inserted into the center of the flame. The contact time with the flame was strictly controlled to 3 seconds, and then the sample was quickly removed while a stopwatch was started. The time was stopped when the flame of the sample was completely extinguished, and the recorded time was the self-extinguishing time. If the sample continued to burn until it was completely carbonized after the flame was removed, it was recorded as "not extinguished". The average value of the three test results for each group was taken as the final self-extinguishing time of that sample. By measuring the self-extinguishing time of the flame-retardant gel polymer electrolytes prepared in Examples 1-5 and Comparative Example 1, their flame-retardant performance was quantitatively evaluated, and the flame suppression ability and self-extinguishing characteristics of the gel system under fire conditions were verified. The results are shown in Table 1. Table 1 Self-extinguishing time detection
[0036] As shown in Table 1, compared to Comparative Example 1, the self-extinguishing time of the electrolyte was shortened after adding flame-retardant additives in Examples 1-5, indicating an improvement in flame-retardant performance. This is mainly because iodine free radicals (I·) capture H· and HO· free radicals in the combustion chain reaction, interrupting the chain reaction of the flame. The hydrogen iodide (HI) released by the thermal decomposition of iodine compounds can also dilute oxygen and combustible gases; the phosphorus component decomposes upon heating to generate polymetaphosphoric acid and other coverings, forming a heat-insulating and oxygen-barrier carbon layer on the material surface. The synergistic effect of iodine and phosphorus: iodine "extinguishes" the fire in the gas phase, while phosphorus "builds a wall" in the condensed phase, jointly improving flame-retardant efficiency.
[0037] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of the claims of this invention.
Claims
1. A method for preparing a flame-retardant gel polymer electrolyte, characterized in that, Includes the following steps: 1) Add diethyl iodomethyl phosphate and 1,3-propanesulfonate lactone to an organic solvent containing 1,3-dioxolane and mix well to obtain a mixed solution; 2) Add lithium salt to the mixed solution obtained in step 1) to obtain the precursor solution; 3) The precursor solution obtained in step 2) is dropped onto the electrode surface and assembled into a supercapacitor. Heating is then performed to form a flame-retardant gel polymer electrolyte in situ on the electrode surface.
2. The method for preparing a flame-retardant gel polymer electrolyte according to claim 1, characterized in that, In step 1), the organic solvent containing 1,3-dioxolane is a mixed solution of 1,3-dioxolane and carbonate solvent.
3. The method for preparing a flame-retardant gel polymer electrolyte according to claim 2, characterized in that, The carbonate solvent includes chain carbonates and cyclic carbonates; based on the total volume of the organic solvent (100%), the organic solvent containing 1,3-dioxolane includes 50% to 60% 1,3-dioxolane, 20% to 30% chain carbonates, and 20% to 25% cyclic carbonates.
4. The method for preparing a flame-retardant gel polymer electrolyte according to claim 3, characterized in that, The chain carbonates include at least one of diethyl carbonate and dimethyl carbonate, and the cyclic carbonates include fluoroethylene carbonate and ethylene carbonate.
5. The method for preparing a flame-retardant gel polymer electrolyte according to claim 1, characterized in that, In step 2), the lithium salt is lithium hexafluorophosphate.
6. The method for preparing a flame-retardant gel polymer electrolyte according to claim 1, characterized in that, In step 3), the heating temperature is 60~90℃.
7. The method for preparing a flame-retardant gel polymer electrolyte according to claim 1, characterized in that, In the precursor solution, by mass percentage, the amount of diethyl iodomethyl phosphate added is 3%~7%, the amount of 1,3-propanesulfonate lactone added is 0.3%~1%, the amount of lithium salt added is 12%~15%, and the balance is an organic solvent containing 1,3-dioxolane.
8. The flame-retardant gel polymer electrolyte obtained by the preparation method according to any one of claims 1 to 7.
9. The application of the flame-retardant gel polymer electrolyte of claim 8 in the preparation of supercapacitors.
10. A supercapacitor, characterized in that, Flame-retardant gel polymer electrolyte containing the preparation method according to any one of claims 1 to 7.